MathDungeon: A Digital Game as an Educational Resource for Teaching Mathematics to Middle and High School Students - Lima, Victor Hugo Nascimento; Sousa, Pedro Moises de (Anais do Workshop de Sistemas de Informação (WSIS); 2024: Anais do XV Workshop de Sistemas de InformaçãoDO - 10.5753/wsis.2024.33690, 2024)
This paper discusses the development of an educational digital game, MathDungeon, which aims to provide a more dynamic approach to teaching mathematics in the classroom in a way that assists students in learning. Preliminary results from a public school indicated positive responses, regarding learning, qualifying the game as a potential tool to aid in education, and contributing to debates about the use of digital games in education.